Anticonvulsant activity of atorvastatin against seizure induced by pentylenetetrazole and maximal electroshock in mice - Mohammad Javad Khoshnoud; Nader Tanideh; Samaneh Namdarian (Shiraz University of Medical Sciences, 2015)
Statins are inhibitors of HMG-CoA reductase and inhibit cellular synthesis of cholesterol and isoprenoids. Studies have previously demonstrated the anti-inflammatory and vasoprotective effects of statins on cultured brain cells (astrocytes and microglia) and endothelial cells. Statins have been recently recognized as anti-inflammatory and neuroprotective drugs. Later, neuroprotective effects of statin were reported in various animal disease models and clinical studies. Atorvastatin also prolonged latency (time to appearance of spike potentials) and diminished the amplitude and frequency of spike potentials, which indicate epileptic discharges. In some studies observed that pre-treatment with atorvastatin efficiently reduced seizure activities, hippocampal neuron death, monocyte infiltration and proinflammatory gene expression. In this study the protective effects of atorvastatin on seizures induced by Pentylenetetrazolee (PTZ) and maximal electroshock stimulation (MES) were investigated. Intraperitoneal pentylenetetrazole was used to induce seizures in mice. It was found that atorvastatin (ED50 = 5.12±0.98) has antiseizure effects comparing to control group. Atorvastatin treatment significantly increased the seizure threshold (p<0.01) and decreased the incidence of tonic seizure and death which is induced by intraperitoneal pentylenetetrazole . The effect of atorvastatin on seizure induced by MES in mice was evaluated and the results demonstrated it is not able to produce anticonvulsant activity. Key word: Seizure, Atorvastatin, Pentylenetetrazole, Maximal electroshock.